Hadrian's Wall : Exploring Its Past to Protect Its Future - Alberti, Marta (Archaeopress Publishing, 2022)
Through the voices of over 20 Hadrian's Wall enthusiasts - chosen amongst prominent frontier scholars and archaeologists, re-enactors, curators, walkers and site managers - this volume celebrates the 1900th anniversary of Hadrian's visit to Britain and the building of the Wall. Together, the authors explore issues such as the impact of environmental changes on archaeology and the innovative technologies used in monitoring and managing the Wall and its collections. The book highlights not only the ways in which Hadrian's Wall can be protected for future generations, but also the ways in which it affects the identities of those who work and travel along it. Rather than a retrospective of work undertaken so far, or an attempt to impose theoretical frameworks onto a living landscape, it offers a realistic discussion of current issues and solutions in the exploration, management and protection of Hadrian's Wall, from the point of view of those living, visiting, researching and working along it.